PENGARUH BOUNDARY SYSTEM & DIAGNOSTIC CONTROL SYSTEM TERHADAP CUSTOMER-ORIENTED MEASURES MELALUI EMPLOYEE-ORIENTED MEASURES SEBAGAI VARIABEL INTERVENING - Jordi Layadi; Saarce Elsye Hatane (Business Accounting Review, 2017)
This study aimed to examine the direct influence of boundary system to employee-oriented measures, boundary system to customer-oriented measures, diagnostic control system to employee-oriented measures, diagnostic control system to customer-oriented measures, boundary system and diagnostic control system on customer-oriented measures through employee-oriented measures as an intervening variable. This study used a quantitative approach, and the data obtained by distributing questionnaires to public companies in Indonesia. Data were processed by using smartPLS software. This study showed that there was a positive relationship of boundary system to employee-oriented measures; positive relationship of boundary system to customer-oriented measures; positive relationship of diagnostic control system to employee-oriented measures; positive relationship of diagnostic control system to customer-oriented measures; and positive relationship of employee-oriented measures to  customer-oriented measures in public companies in Indonesia.